2020
DOI: 10.1155/2020/1675987
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Care Uptake and Immediate Outcomes among Discordant Couples Accessing Routine HIV Care in Kenya

Abstract: Introduction. A large proportion of new HIV infections occur within discordant partnerships making discordance a significant contributor to new HIV infections in Africa. Despite the role of preconception care for HIV discordant couples, there is little data on fertility desire and preconception care uptake. This study aimed at documenting fertility desire (desire to conceive), determining the uptake of preconception care, identifying HIV prevention strategies used during preconception care, and determining imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, there is no clear explanation for this observation. Some studies have also reported a relatively high serodiscordant rate among couples [65] and increased use of ARVs. Regular and concurrent characterization of HIV-1 genetic/antigenic variants and mutations that encode resistance in HIV-1 subtypes circulating in the whole country is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no clear explanation for this observation. Some studies have also reported a relatively high serodiscordant rate among couples [65] and increased use of ARVs. Regular and concurrent characterization of HIV-1 genetic/antigenic variants and mutations that encode resistance in HIV-1 subtypes circulating in the whole country is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Regular periodic molecular analysis of HIV-1 strains is important, especially now that subtype-specific vaccines are under consideration. Regular resistance mutation analyses are required to monitor ARV resistance and determine the association between HIV-1 strain variation(s) and high infection discordance seen among some couples in Kenya [65]. Characterization of genetic/antigenic variants circulating in a given population is essential for more effective patient management.…”
Section: Characterization Of Hiv-1 Genetic/antigenic Variants Circula...mentioning
confidence: 99%
“…With the scale-up of HHC evaluation, there is an opportunity to increase the value of this service by integrating HIV screening to identify SDCs in TB-affected households (i.e., households in which at least one family member has been diagnosed with TB). Past studies have shown high PrEP uptake, adherence [18][19][20][21][22] and acceptability [18,23] among SDCs, reporting that couple-focused ART and PrEP services were perceived to strengthen couples' relationships [24] and could help support safer conception among couples desiring pregnancy [21,22]. Thus, HHC evaluation may provide an excellent opportunity to improve linkage to HIV care and PrEP among SDCs and prevent HIV acquisition and adverse health effects.…”
Section: Introductionmentioning
confidence: 99%